Pelatihan Kerja, Soft Skill dan Hard Skill Mendorong Peningkatan Kinerja Karyawan - Wahyu Astutik; M. Sulhan (JMK (Jurnal Manajemen dan Kewirausahaan), 2022)
This study aims to measure the extent to which employee competencies represented by training, soft skills and hard skills affect employee performance. This study also describes the new findings as a development of previous research. The method used is descriptive quantitative with a total of 100 respondents from CV. Sentosa’s employees. The independent variable (X) in this study is Training, Soft Skill, and Hard Skill. Meanwhile, the dependent variable (Y) in this study is Employee Performance. The results showed that The X’s variables had a significant positive effect on employee performance. The results of the partial test of this study indicate that the ability of hard skills has less effect on increasing employee performance. This study also shows an R2 value of 0.682 which means that this model is able to provide an explanation of various variations of the dependent variable by 68%.